PTU-108 Sustainibility of The Impact of Nutrition Support Team (NST) at a District General Hospital-5 Year Results. (17th August 2016) - Eaton, K; Copeland, E; Roberts, H; Patel, M; Perry, L; Gupta, S; Tarn, A
Abstract : Introduction: Although in 2010 Croydon University Hospital had Parenteral Nutrition (PN) team, it was felt patient care could be improved by broadening the team's scope and extending its influence. Audit showed that despite Trust policy on PN use, it was non-compliant with NCEPOD recommendations. This was a key driver to form a Nutrition Support Team (NST) in October 2010. Our aims were to reduce inappropriate use of PN and emergency PN, ensure administration through central venous catheters and encourage EN where appropriate. This analysis was to check for sustainability of impact of NST after 5 years. Methods: In 2010 NST members included a Chemical Pathologist, Gastroenterologist, Dietitian and Pharmacist. In 2012, a Consultant Biochemist, Dietitian joined the team. Protocols were drawn up, ratified and made available on a NST link on Trust Intranet. Patients requiring PN had to be discussed with NST. Radiology Department was contacted for timely insertion of peripheral inserted central venous catheters (PICC). Medical and nursing staff were trained on care of lines and appropriate use of PN. Results: Results are shown in the Table. Use of peripheral cannulae for PN has gone down from 31% in 2009/10 to 4% in 2010/11 to 0% since 2011/12.Cost savings have been made in a number of areas. In 2010/11, savings of £20, 671 were made. In 2013, NST advised and implemented a change in supplier of PN bags, resulting in total cost savings of £19, 822. The total number of referrals for PN, number of inappropriate referrals, use of emergency PN, number of patients requiring PN for <5 days has fallen while total number of days of PN and the mean have increased perhaps indicating more appropriate use of PN. Conclusion: Our intervention resulted in safer, coordinated and appropriate delivery of PN which has been sustained over 5 years. The feedback from hospital management, clinical staff has been positive and encouraging. These results may be extrapolated to all hospitals that care for patients requiring parenteral nutrition. Disclosure of Interest: None Declared